Effect of thermal profile on a shift in phase transition temperature of Sb-doped KNN piezoceramic - Jirapa Tangsritrakul; Phieraya Poolphol; Wanwilai Vittayakorn (Ferroelectrics, 2021)
This work investigated the impact of the thermal profile in the shift of phase transition temperature for KNNS piezoceramic, using high-resolution synchrotron x-ray powder diffraction (SXPD) and dielectric measurement. The temperature-dependent dielectric permittivity and SXPD profile showed that all phase transformations occurred at higher temperature under heating than under cooling. Moreover, under cooling from 227 °C to −163 °C and reheating to 227 °C, none of the unit-cell volumes fully recovered to their initial size. These results suggest that the change in unit-cell volume under heating/cooling plays a significant role in the shift of phase transition temperatures that was observed.
Keywords: Ferroelectric and Piezoelectric Materials; Acoustic Wave Resonator Technologies; Microwave Dielectric Ceramics Synthesis